To solve for y and change the equation from standard form to slope-intercept form, we'll rearrange the equation 8x - 4y = 24.
8x - 4y = 24
Let's begin by isolating the term with y on one side of the equation:
-4y = -8x + 24
Next, divide every term of the equation by -4 to solve for y:
y = (-8x + 24)/(-4)
Simplifying the equation further:
y = 2x - 6
Thus, the equation is now in slope-intercept form (y = mx + b), where m represents the slope (m = 2) and b represents the y-intercept (b = -6).
Change the equation from standard form ti slope intercept form by solving
For y 8x-4y-=24
1 answer